Suburbanisation Processes of Cracow’s Suburban Areas - Musiał-Malagó, Monika (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The processes of suburbanisation are taking place more and more intensively around Polish cities. The dynamics and range of this phenomenon carry a number of negative consequences. The aim of this paper is to present the changes that took place in the suburban areas of the city of Cracow as a result of suburbanisation in the years 2003-2012. To determine the extent of this process, the following were analysed: changes in the population, the size and directions of migrations, and the amount of agricultural land not used for farming with regard to the aim of exclusion.